Monitoring temperature & smoke for substations using GSM Technology: article / Amran Ayub - Ayub, Amran
This paper is prepared as to introduced the GSM technology in the current substation monitoring, for wireless and data sending purposes. The purpose of this system is to remotely monitor and control the operational status of the substations by mobile monitors and control system. A remote monitoring is needed as to cut the maintenance cost and time. Maintenance is a key activity as for utilities as to assure the proper operation of their network [1]. Among effective maintenance characteristics is the low cost implementation, since it is known, that many small and medium sized corporations are hesitating to apply a wireless monitoring due to high investment reason[2j. Here, GSM technology helps to enhance the remote monitoring that requires constant updating status of a substation to the mobile operators and control centre. Its network is serves as a medium for transmitting the remote signal[3] and consist of monitoring part and monitoring centre. The computer and the monitoring device is attached via MAX232, along with GSM module for transmitting SMS to the mobile operator. The result shows that such monitoring that is based on GSM application can be realized.